Black liquor-derived carbonaceous solid acid catalyst for the hydrolysis of pretreated rice straw in ionic liquid. (November 2016) - Bai, Chenxi; Zhu, Linfeng; Shen, Feng; Qi, Xinhua
Graphical abstract: Highlights: Carbonaceous solid acid catalyst was prepared from rice straw-derived black liquor. KOH acting as both lignin extracting agent and activation agent of carbon material. The solid acid catalyst showed good activity for hydrolysis of pretreated rice straw. A maximum TRS yield of 63.4% was obtained from the KOH pretreated rice straw. A renewable strategy for utilization of all components of lignocellulosic biomass. Abstract: Lignin-containing black liquor from pretreatment of rice straw by KOH aqueous solution was applied to prepare a carbonaceous solid acid catalyst, in which KOH played dual roles of extracting lignin from rice straw and developing porosity of the carbon material as an activation agent. The synthesized black liquor-derived carbon material was applied in catalytic hydrolysis of the residue solid from the pretreatment of rice straw, which was mainly composed of cellulose and hemicellulose, and showed excellent activity for the production of total reducing sugars (TRS) in ionic liquid, 1-butyl-3-methyl imidazolium chloride. The highest TRS yield of 63.4% was achieved at 140 °C for 120 min, which was much higher than that obtained from crude rice straw under the same reaction conditions (36.6% TRS yield). Overall, this study provides a renewable strategy for the utilization of all components of lignocellulosic biomass.